Spontaneous ovarian hyperstimulation syndrome following evacuation of a partial mole: a case report - Sehgal, Chandni; Chakarabarti, Sekhar; Sareen, Ravmeet K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Ovarian hyperstimulation syndrome (OHSS) is usually an iatrogenic complication of ovarian stimulation, while spontaneous OHSS is rare and linked to conditions with high human chorionic gonadotropin (hCG), such as molar pregnancy. Herein, this case reports an 18-year-old woman who developed spontaneous OHSS two months after suction evacuation of a partial mole, presenting with abdominal pain, vomiting, and distension. Her β-hCG had fallen from 59,027 to 1,463 mIU/ml. Ultrasonography showed bilaterally enlarged multicystic ovaries ( 8–9 cm), ascites, and an empty uterus; laboratory parameters were normal. Pregnancy, ovarian torsion, and persistent mole were excluded, confirming spontaneous OHSS. She was treated conservatively with cabergoline 0.5 mg daily for 10 days, with resolution of symptoms in 4–5 days, and discharged on combined oral contraceptives. β-hCG remained normal over 2 years of follow-up. This case underscores the rarity of spontaneous OHSS post-molar evacuation and the importance of early recognition and conservative management for favorable outcomes.